NEUROPROTECTIVE EFFECT OF POTENT ANTIOXIDANT LYCOPENE IN STRESS INDUCED RAT PC-12 CELLS - NUPUR S. SRIVASTAVA; DEEPTI DUA (International Journal of Pharma and Bio Sciences, 2015)
Neurodegenerative diseases like Parkinson’s disease (PD),Amyotrophic Lateral Sclerosis (ALS) and Schizophrenia are a group of illness with diverse clinical importance and etiologies. Oxidative stress in which production of highly reactive oxygen species (ROS) and reactive nitrogen species (RNS) overwhelms antioxidant defences, is a feature of many neurological diseases. Lycopene, the most potent antioxidant among various common carotenoids, protects against the threat of neurodegeneration and works as a neuroprotective agent by preventing mitochondrial dysfunctions, microglia activation and focal cerebral ischemia in rats. To study the antioxidant properties of lycopene, the levels of antioxidant enzymes such as catalase (CAT), superoxide dismutase (SOD) & glutathione-S-transferase (GST) and non-enzymatic parameters such as glutathione (GSH) and lipid peroxidation were analyzed in PC-12 cells treated with 6-hydroxydopamine (6-OHDA) and lycopene. DPPH and FRAP assay was done to check the total antioxidant capacity of lycopene. Cell viability was also determined using MTT assay in these samples. Cell Morphology was also studied using TUNEL ASSAY prior and after treatment of cells with 6-OHDA and Lycopene. Since 6-OHDA is a neurotoxic agent, it caused a decrease in levels of antioxidant enzymes, SOD, CAT, GST, GSH and cell viability. Lipid peroxidation levels were increased in PC-12 cells after treatment with 6-OHDA. Total antioxidant levels were found to be increased in cells treated with 6-OHDA and lycopene as compared to cells treated with 6-OHDA alone. But on further treatment of cells exposed to 6-OHDA with lycopene, the levels of these enzymes and the cell counts were increased to nearly 80% as compared to the control and lipid peroxidation levels were decreased to 75% as compared to the control. Altered activities of these antioxidant enzymes upon treatment with 6-OHDA were restored to almost normal level upon treatment of cells with lycopene. This may be due to the antioxidant property of lycopene, which regulated the neuronal cells’ defense system against neurotoxic shock.